The biophysical effects of potential changes in irrigated crops on diurnal land surface temperature in Northeast China - Li, Xintao; Hai, Quansheng; Xia, Ke; Vandansambuu, Battsengel; Bao, Yuhai (Frontiers in Ecology and Evolution, 2023)
Irrigated crops have experienced a significant global expansion. The study of the biophysical response of climate change to irrigated crop expansion in different regions, particularly in terms of monitoring the mechanisms of daytime and nighttime land surface temperature (diurnal LST), however, remain insufficiently explored. In this study, we combined the window-searching strategy to characterize the spatial-temporal distribution patterns of LST, and the driving mechanisms. The results showed that irrigated crop expansion led to daytime cooling (2.11±0.21°C, 97.4%) and nighttime warming (0.64±0.19°C, 79.9%). Daytime LST change had a negative correlation with latent heat flux change (63%), but a positive correlation with solar radiation energy and heating potential term change (91% and 77%). The heating potential term produces a cooling effect during the day and a warming effect at night. The explanatory power of the single factor (the mean of q<0.50) of land surface energy for diurnal LST variation was significantly smaller than that of the * Corresponding author.